1994
DOI: 10.1007/bf00788678
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the inotropic and arrhythmogenic action of the sodium channel activator BDF 9148: a comparison to its S-enantiomer BDF 9196, to its congener DPI 201-106, to norepinephrine, and to ouabain

Abstract: Positive inotropic substances which enhance the myocardial cAMP level or inhibit the Na+/K(+)-ATPase are known for their proarrhythmic side-effects. This study was performed to investigate the inotropic and arrhythmogenic action of the Na(+)-channel activator BDF 9148 (racemate) in comparison to its S-enantiomer BDF 9196, its congener DPI 201-106 (racemate), to norepinephrine, and to ouabain. In 30 open-chest dogs, the effects of these substances on the first derivative of left ventricular pressure (dP/dt, Mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Studies in vivo have also shown that Na ϩ channel enhancers increase cardiac contractile performance in anesthetized dogs with acute ischemia (Baumgart et al, 1994) and in the chronic microembolization-induced failing heart model (Taniumra et al, 2000). However, no prior study has systematically investigated the effect of a Na ϩ channel enhancer on hemodynamic and cardiac function in the conscious animal with heart failure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies in vivo have also shown that Na ϩ channel enhancers increase cardiac contractile performance in anesthetized dogs with acute ischemia (Baumgart et al, 1994) and in the chronic microembolization-induced failing heart model (Taniumra et al, 2000). However, no prior study has systematically investigated the effect of a Na ϩ channel enhancer on hemodynamic and cardiac function in the conscious animal with heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that inotropic agents that increase cellular calcium may act centrally to increase vagal tone in dogs with heart failure . Interestingly, the negative cardiac chronotropic response to LY341311 was not found in normal dogs, either under anesthetic (Baumgart et al, 1994) or fully conscious (Gill et al, 2002). It is well known that heart failure is associated with derangements of autonomic control of the cardiovascular system, manifested as reduced parasympathetic activity and elevated sympathetic activity (Kinugawa and Dibner-Dunlap, 1995;Wang et al, 1999).…”
Section: Tablementioning
confidence: 95%
See 1 more Smart Citation
“…Activators of the main cardiac sodium channel Nav 1.5 increase contractility. 5,22 Activation of Nav 1.5 , however, also prolongs repolarization 5,22 and provokes ventricular arrhythmias. 23 Tetrodotoxin-sensitive sodium channels contribute to sodium influx and increased contractility in the heart: Approximately 25% of mammalian cardiac sodium channels are tetrodotoxin sensitive, and preferentially localized close to the T tubules.…”
Section: Main Findingsmentioning
confidence: 99%
“…4 Activators of cardiac sodium channels are known to not only exert positive inotropic effects but also cause arrhythmias. 5 Cardiac sodium channels can be divided into tetrodotoxin-resistant (µmol/L range) and tetrodotoxin-sensitive (nmol/L range) channel subtypes. 4 The main isoform of the tetrodotoxin-resistant sodium channels Nav 1.5 is expressed predominantly in cardiomyocytes.…”
mentioning
confidence: 99%